Heat Transfer Improvements in Axial Flux Permanent Magnet Traction Motor - Rahul Roy; Sivakumar Ramasami; Lenin Natesan Chokkalingam (IEEE Access)
Axial Flux Permanent Magnet Motors (AFPM) have high torque density and power density. However, efficient heat removal is crucial for its proper functioning and longevity. In this paper, a 6 kW AFPM motor is designed for an e3W cargo, operating at a speed of 45 km/h. The calculation of different losses from electromagnetic analysis serves as the heat input for thermal analysis. With a current density exceeding 10 A/mm2, liquid cooling is preferred for the AFPM motor. To determine the optimal number of spirals in the cooling jacket casing, sensitivity analysis for the number of spirals was conducted and the wall heat transfer coefficient (WHTC) has been determined through analytical equations and computational fluid dynamics (CFD). Furthermore, this paper discusses the impact of different curvature shapes which are kept at $90^{0}$ and another at $45^{0}$ angles to improve heat transfer rate and thereby reducing the temperature in coils, stator core and rotor core which leads to improved torque density and power density of the AFPM motor.